Dynamics analysis of the two-layer complex propagation network with individual heterogeneous decreased behavior - Tian, Yang; Tian, Hui; Zhu, Xuzhen; Cui, Qimei (Frontiers in Physics, 2023)
Due to the differences of society stratum, personal profession and social acceptability, information propagation can be impacted by the contact capabilities of individuals. Importantly, we found that with the changes in individual psychology, their response to a phenomenon will gradually weaken. The phenomenon is called heterogeneous decreased behavior, and applied in the fields of economics, sociology and ecology. In social network, person show gradually decreasing degree of interest for an information, named individual heterogeneous decreased behavior (IHDB). Then, we structure a two-layer network model to describe individual behavioral contact, and propose a threshold function to represent IHDB behavior. Meanwhile, we use a partition theory to explain information propagation mechanism. Through experiments, there is a continuous information outbreak in the ultimate adoption size when individuals behave a positive IHDB. When individuals behave a passive IHDB, however, there is a discontinuous information outbreak in the ultimate adoption size. Eventually, our experiments show that the theoretical analysis matches the results of the simulations.